Numerical Simulation of Parameters Optimization for Goaf Gas Boreholes - Jiajia Liu; Jianliang Gao; Ming Yang; Dan Wang; Liang Wang (Advances in Civil Engineering)
In view of the ground drilling of the N2206 working face in Shanxi Wangzhuang Coal Mine, the gas concentration is low and the extraction effect is not good. Fluent computational fluid dynamics software was used to simulate the ground extraction drilling position of the N2206 working face in the goaf (the distance from the top of the coal seam and the distance from the return to the wind). The numerical simulation results show that when the final hole of the ground extraction hole in the goaf is 16 m from the roof of the coal seam and the distance from the return air is 45 m, the extraction effect is optimal. The average extraction gas volume is 9.78 m3/min, and the average extraction gas concentration is 43.95%, the best extraction effect is obtained. After optimizing the ground drilling position in the goaf and combining with the site implementation, the maximum gas scouring amount of the extraction is 12.59 m3/min, which is 3.42 m3/min higher than the original. The maximum gas concentration of extraction was 63.54%, which was 28.82% higher than the original. After optimization, the gas concentration of the extraction is more than 30%, and the extraction effect is very good. Field application results further validate the reliability of theoretical analysis and numerical simulation results.